2013
DOI: 10.1242/jcs.136580
|View full text |Cite
|
Sign up to set email alerts
|

Pain modulators regulate the dynamics of PKA-RII phosphorylation in subgroups of sensory neurons

Abstract: Knowledge about the molecular structure of protein kinase A (PKA) isoforms is substantial. In contrast, the dynamics of PKA isoform activity in living primary cells has not been investigated in detail. Using a high content screening microscopy approach, we identified the RIIb subunit of PKA-II to be predominantly expressed in a subgroup of sensory neurons. The RIIb-positive subgroup included most neurons expressing nociceptive markers (TRPV1, NaV1.8, CGRP, IB4) and responded to pain-eliciting capsaicin with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 52 publications
5
72
0
Order By: Relevance
“…We complemented this data by analyzing the expression of two kinase isoforms, PKA-RIIβ and CaMKIIα, involved in pain sensitization of nociceptors (Brüggemann et al, 2000;Chen et al, 2010;Isensee et al, 2014a). With the exception of CaMKIIα, all marker proteins were already detectable at birth, but changed their cellular expression pattern during aging ( Figs 2B and 3).…”
Section: Basal Characterization Of Sensory Neurons Rats From P0 To 24mentioning
confidence: 96%
See 4 more Smart Citations
“…We complemented this data by analyzing the expression of two kinase isoforms, PKA-RIIβ and CaMKIIα, involved in pain sensitization of nociceptors (Brüggemann et al, 2000;Chen et al, 2010;Isensee et al, 2014a). With the exception of CaMKIIα, all marker proteins were already detectable at birth, but changed their cellular expression pattern during aging ( Figs 2B and 3).…”
Section: Basal Characterization Of Sensory Neurons Rats From P0 To 24mentioning
confidence: 96%
“…We have recently shown that regulatory subunit PKA-RIIβ identifies not only some, but the large majority, if not all, different nociceptive subgroups (Isensee et al, 2014a). If this integrative marker of all nociceptive neurons develops before, after, or simultaneously with the establishment of nociceptive subgroups as defined by Nav1.8 or TRPV1 expression has not been analyzed.…”
Section: Pka-riiβ Expression Precedes That Of Nociceptive Subgroup Mamentioning
confidence: 99%
See 3 more Smart Citations